Analysis Fishermen Household Income of Fisheries and Non Fisheries Sector In Mendol Island Kuala Kampar Subdistric Pelalawan Regency of Riau Province - Zhurayda '; Eni Yulinda; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This Study was conducted in October 2016 in the Mendol Island Pelalawan district of Kuala Kampar in Riau Province. The method used in this research is survey method. Fishermen household in Teluk village is 220 FH’s, consisting of 80 FH’s using Gombang fishing gear, and 140 FH’s using Nets fishing gear. To facilitate the researcher, 10% of the RTP is taken, so that the sample of respondents using Gombang 8 RTP fishing equipment, and the sample of respondents who use the fishing gear as much as 14 FH’s. So the respondents are to 22 FH’s. Based on the results of research that has been conducted on the income of fishermen households from fisheries and non fisheries sector in Mendol Island Kuala Kampar sub district Pelalawan Riau Province can be drawn some conclusions, namely: 1) fisherman income from the fishery sector IDR. 40.350.000 per year (gombang) and IDR. 12.455.000 per year (net). Revenue from non-fishery sector IDR. 12,725,491 per year (gombang) and IDR. 13,333,333 per year (net). Fishermen income IDR. 53,075,491 per year (gombang) and IDR. 25,788,333 per year (net); 2) income contribution from non-fishery sector to total income of fisherman household in Teluk is 62,16%, meanwhile income contribution from non fishery sector to total fisherman household income in Gulf is equal to 37,84%. Keywords: Revenue, Fishery, Non Fishery, Mendol Island.